Analisis Tingkat Literasi Wakaf Uang pada Mahasiswa Ekonomi Syariah di Kabupaten Nganjuk - Ahmad Maulana; Masfufah Masfufah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the level of cash waqf literacy among Islamic Economics students in Nganjuk Regency and to identify the supporting and inhibiting factors affecting cash waqf literacy. The research employed a quantitative approach using a descriptive method. Data were collected through questionnaires distributed to 74 respondents from STAIM Nganjuk and Universitas Pangeran Diponegoro Nganjuk. The sampling technique used the Slovin formula, while the data analysis applied the Cash Waqf Literacy Index (CWLI) method based on the Waqf Literacy Index concept developed by Puskas BAZNAS. The measurement was conducted through three dimensions: knowledge, understanding, and capability related to cash waqf. The results showed that the level of cash waqf literacy among Islamic Economics students in Nganjuk Regency was categorized as moderate or developing. The knowledge dimension scored 68.71, the understanding dimension scored 72.80, and the capability dimension scored 69.98. The findings indicate that students generally understand the basic concept of waqf; however, they still have limited understanding regarding the management, regulation, and implementation of cash waqf as a productive economic instrument. Supporting factors of cash waqf literacy include education, social media, religious organizations, and access to digital information. Meanwhile, the inhibiting factors include the lack of socialization, limited practical education regarding cash waqf, and low public trust in the transparency of waqf management institutions. Therefore, strengthening education, innovating waqf programs, and building multi-stakeholder collaboration are necessary to improve cash waqf literacy among students and society sustainably.